Kids get coding. Online safety for coders - Lyons, Heather (Heather K.); Tweedale, Elizabeth (Lyons, Heather (Heather K.). Kids get coding., 2017)
How can you stay safe while surfing the Internet? You need to be an Internet superhero! Find out how information is used online and how you can protect your identity while also enjoying the Internet.